Find (w² - w + 1) + (w³ - 2w² + 99).
2 answers:
Step-by-step explanation:
Given
(w² - w + 1) + (w³ - 2w² + 99)
Now opening the bracket we get
w² - w + 1 + w³ - 2w² + 99
Re arranging,
w³- 2w²+w²- w+ 1+ 99
w³- w²- w+100
Thus the answer is w³- w²- w+100
Answer:
w³ - w² - w + 100
Step-by-step explanation:
The sum of (w² - w + 1) and (w³ - 2w² + 99) is:
(w² - w + 1) + (w³ - 2w² + 99)
= w² - w + 1 + w³ - 2w² + 99
= w² - 2w² - w + w³ + 99 + 1
= -w² - w + w³ + 100
= w³ - w² - w + 100
Thus, (w² - w + 1) + (w³ - 2w² + 99) = w³ - w² - w + 100.
You might be interested in
Answer:
Step-by-step explanation:
your equation shown above is set up incorrectly in order to solve this i need the right equation you must plug in each number to q to find the right solution
Do you know the answer???
Answer:
123123 3213123 12312 dasdsd aw dasd sda asdasd
Step-by-step explanation:
I think the answer is 3.45$ for one person.
Here hope this help the solution is X= -2 and y=9